Old enemies make the best lovers - Sebastian, Kate ([place of publication not identified] [publisher not identified], 2014)
Christy Martinez may have been a nerd and the number one victim for the mean girls in her high school, but she’s since grown up, gone to college, and carved out a successful career for herself. Now in her late 20s, she’s put high school behind her, only to be blindsided by a blast from her past. She and her friends have planned a much-needed vacation, but she finds out at the last minute that they’ll be joined by uber rich and gorgeous Kyle Quinto. He just happens to be the guy who played a cruel trick on her in high school, breaking her heart and making her a target for bullying in the process. Can Christy forgive and forget? Because Kyle is a whole lot of hot.
Keywords: Philippine fiction (English)